2021
DOI: 10.17507/tpls.1106.02
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Individual Support for Ethnic Minority Preschoolers in the Silent Period in Learning Chinese

Abstract: The silent period is most frequently used to describe the period of second language (L2) acquisition where the learner displays no obvious language output. In Hong Kong, ethnic minority (EM) preschoolers face challenges on home, school and community levels in learning Chinese as a second language, meaning that for those in the silent period, it may particularly difficult to begin speaking Chinese, leading to slower language development. A support service was established, targeting EM preschoolers in Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Our investigation revealed an array of communication strategies (e.g., nonverbal communication, participation) used by emergent bilingual children during the early stage of L2 acquisition. Several included studies indicated that children's expressive language does not appear all at once but emerges incrementally (Cekaite, 2007;Ervin-Tripp, 1974;Gibbons, 1985;Saville-Troike, 1988;Tse et al, 2021). These findings align with existing literature on young children's capacity to generate alternative solutions to problems (Barnes et al, 2018;Lambert, 2001;Marulis & Nelson, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our investigation revealed an array of communication strategies (e.g., nonverbal communication, participation) used by emergent bilingual children during the early stage of L2 acquisition. Several included studies indicated that children's expressive language does not appear all at once but emerges incrementally (Cekaite, 2007;Ervin-Tripp, 1974;Gibbons, 1985;Saville-Troike, 1988;Tse et al, 2021). These findings align with existing literature on young children's capacity to generate alternative solutions to problems (Barnes et al, 2018;Lambert, 2001;Marulis & Nelson, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…"Gamebased Learning" approach was used to leverage the immersive nature of video games for effective L2 instruction (Mfeka & Thomson, 2019). Additionally, "Targeted Individual Support" provides one-on-one L2 tutoring, emphasizing vocabulary growth and better communication skills (Tse et al, 2021).…”
Section: Classroom Contextsmentioning
confidence: 99%